Onscreen/Offscreen - Nakassis, Constantine V. (University of Toronto Press, 2023)
Based on over a decade of ethnographic fieldwork in the South Indian state of Tamil Nadu, Onscreen/Offscreen is an exploration of the politics and being of filmic images. The book examines contestations inside and outside the Tamil film industry over the question "what is an image?" Answers to this question may be found in the ontological politics that take place on film sets, in theatre halls, and in the social fabric of everyday life in South India, from populist electoral politics and the gendering of social space to caste uplift and domination. Bridging and synthesizing linguistic anthropology, film studies, visual studies, and media anthropology, Onscreen/Offscreen rethinks key issues across a number of fields concerned with the semiotic constitution of social life, from the performativity and ontology of images to questions of spectatorship, realism, and presence. In doing so, it offers both a challenge to any approach that would separate image from social context and a new vision for linguistic anthropology beyond the question of "language."